KEANEKA RAGAMAN DEWAN KOMISARIS DAN KOMITE AUDIT "PERSPEKTIF TATA KELOLA" DIHADAPKAN DENGAN KINERJA KEUANGAN - Piter Nainggolan (JURNAL LENTERA AKUNTANSI, 2020)
The purpose of this study is to gain a better understanding of how an integrated and expanded corporate governance model explains the relationship between the structure of corporate governance and the financial performance of companies in companies listed on the Indonesia Stock Exchange. This study also examines the influence of the background of the board of commissioners, citizenship of the board of commissioners, independent board of commissioners, and audit committee on corporate financial performance. This study is unique in that we analyze the diversity of the board of commissioners' committees to gain broader insights on how to share the diversity of board functions and shareholder value on the Indonesia Stock Exchange. The sample studied was based on companies listed on the Indonesia Stock Exchange in 2015-2017. Data is collected using quantitative techniques from secondary sources from the company's annual report to be studied. Based on test results using panel data regression, it can be concluded that: (1) The background of the board of commissioners has a significant influence on the company's financial performance; (2) The citizenship of the company's Board of Commissioners does not have a significant influence on the company's financial performance. (3) Independent Board of Commissioners does not have a significant influence on the Company's Financial Performance; and (4) The Audit Committee has a significant influence on the Company's Financial Performance.Keywords: Background of the board of commissioners, citizenship of the boardof commissioners, independent board of commissioners, audit committee